Bird Flu as Next Health Risk for Human Being - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2025)
Pepole are protected by H5N1 strains already circulating as well as by vaccinated healthy volunteers. The treat of a new infections from wild bird is spreading among animals that provide us with milk and are causing disease in people. It is possible that the capacity to attache to human cells and then to spread and to develop mutations allowing seasonal fly to exchange genetic information and spreading by a new strain. Therefore the need to develop a new vaccine that could be used in case of outbreak.